Age Pattern at Menarche as Results from a Puberty Survey - Naereintheni A/P Ganabathy; Anggraini Widjajakusuma; Dini Hidayat (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Range age of menarche is 15 to 17 years old from 1950’s to 20th century. However, in the current generation, the menarche age ranges from 13 to 16 years old. The factors affecting the change in the age of menarche over time and individual variation are due to the genetic or environmental factors. This study was performed to determine age pattern at menarche in Jatinangor, Sumedang ,West Java, Indonesia.Methods: The data for this descriptive study was obtained from a puberty survey performed by faculty members of Faculty of Medicine Universitas Padjadjaran from April–September 2013 in Jatinangor, Sumedang, West Java. A total of 249 female respondents aged 11–70 years old were included in this study. The age and year onset of menarche was determined and analyzed using computer.Results: The range age of menarche in Jatinangor population from early 1963 until 2013 was 9–17 years old, with 0.8% (n=2) cases of precocious puberty in current generation (year onset of menarche, year 2004–2013). For the onset of menstruation, the current generation had a youngest age compared to the other older generations with a mean age of 12.28 years old. Furthermore, most of the respondents from the current generation reached menarche at the age of 12 years old (37.4%). Conclusions: The onset of menarche in current generation is earlier compared to the older generations with most of them reaching menarche at the age of 12 years old. [AMJ.2016;3(4):640–3] DOI: 10.15850/amj.v3n4.952